Toxocariasis and Ingestion of Raw Cow Liver in Patients with Eosinophilia - Choi, Dongil (The Korean Society for Parasitology, 2008)
Ingestion of raw animal liver has been suggested as a possible mode of infection of human toxocariasis. We evaluated the relationship between toxocariasis and the ingestion of raw meat in patients with eosinophilia of unknown etiology. The study population consisted of 120 patients presenting with peripheral blood eosinophilia (> 500 cells/µl or > 10% of the white blood cell count). They were divided into 2 groups: 104 seropositive patients based on a Toxocara excretory-secretory IgG ELISA and 16 seronegative patients. While 25.0% of seronegative patients had a recent history of eating raw cow liver, 87.5% of seropositive patients had this history. Multivariate statistical analysis showed that a recent history of eating raw cow liver was related to an increased risk of toxocariasis. Collectively, it is proposed that raw cow liver is a significant infection source of toxocariasis in the patients with eosinophilia of unknown etiology.